2017
DOI: 10.1186/s40623-016-0596-9
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal structure in electron density at mid-latitudes: upward-propagating tidal effects

Abstract: This work studies the upward-propagating migrating and non-migrating tidal effects from the lower atmosphere on the longitudinal variation of electron density ( Ne) in both the E and F regions at mid-latitudes during the 2002 March equinox. A total of 12 runs are conducted using the Thermosphere Ionosphere Electrodynamic General Circulation model for theoretical investigation. The Ne at altitudes above 200 km is affected by upward-propagating tides, with maximum values attained around 300 km. Migrating tides r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 57 publications
1
11
0
1
Order By: Relevance
“…On the other hand, a four‐peak longitudinal structure of zonal winds can be seen in model simulations in the nighttime during equinox (see Figure c). The strong DE3 nonmigrating tidal component from the lower atmosphere, which can lead to the four‐peak longitudinal patterns in zonal winds (Oberheide et al, ; Wang & Lühr, , Wang & Zhang, ; Xiong et al, ), is suggested to be caused by the latent heat release. The longitudinal patterns of zonal winds can modulate the ionospheric dynamo electric fields and have strong influence on the dynamics in the upper thermosphere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a four‐peak longitudinal structure of zonal winds can be seen in model simulations in the nighttime during equinox (see Figure c). The strong DE3 nonmigrating tidal component from the lower atmosphere, which can lead to the four‐peak longitudinal patterns in zonal winds (Oberheide et al, ; Wang & Lühr, , Wang & Zhang, ; Xiong et al, ), is suggested to be caused by the latent heat release. The longitudinal patterns of zonal winds can modulate the ionospheric dynamo electric fields and have strong influence on the dynamics in the upper thermosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the geomagnetic field can also significantly influence the distribution of the plasma in the ionosphere. There have been reports that the ionosphere electron density and plasma drifts also have large longitudinal variations (e.g., Maute et al, ; Su et al, ; Wang et al, ; Wang & Zhang, ; Zhong et al, ). These produce large longitudinal variations of ion drag over different latitudes and local times.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4 shows the geographic longitude and latitude variations of the disturbed electron density, vertical plasma velocity, meridional plasma velocity, and neutral temperature. The enhancements of wind and temperature at -60°~-180° GLon might be related to the longitudinal patterns of electron density, which have a peak at America sector and causing by the topology of geomagnetic eld (Wang and Zhang, 2017;Zhang et al, 2019). The wind and temperature can be affected by electron density via ion-neutral collision.…”
Section: Broken Mean Circulationmentioning
confidence: 99%
“…There are distinct longitudinal (zonal) differences in the ionospheric electron density and thermospheric mass density. The midlatitudinal electron density exhibits obvious wave‐2 and wave‐1 variations along geographic longitudes (GLon) in the Northern and Southern Hemispheres, as revealed by observations from both ground‐based Global Positioning Satellite (GPS) receivers and the Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) and Challenging Minisatellite Payload (CHAMP) satellites, as well as by global simulations [ Zhang et al , , , ; Xu et al , ; Luan and Dou , ; Xiong and Lühr , ; Wang et al , , ; Wang and Zhang , ]. As its thermospheric counterpart, the mass density exhibits a wave‐1 longitudinal structure, which is almost 180° out of phase in the two hemispheres, as revealed by both CHAMP observations and simulations using the Global Ionosphere‐Thermosphere Model (GITM) [ Xiong et al , ; Wang et al , ].…”
Section: Introductionmentioning
confidence: 99%